Proportionate Reduction in Uncertainty of Late Onset Infection in Pre-term Infants by Neutrophil CD64 Measurement. (1st February 2014) - Berrington, Janet Elizabeth; Hearn, Richard Iain; Hall, Chris; Stewart, Christopher James; Cummings, Stephen Paul; Embleton, Nicholas David
<x xml:space="preserve">Abstract</x> Objective: Establish how neutrophil CD64 performs as a marker of definite infection in pre-term infants in comparison to C reactive protein (CRP) and procalcitonin (PCT). Methods: A total of 38 pre-term infants with suspected late onset infection had CD64 measured by flow cytometry. Proportionate reduction in uncertainty (PRU) curves were generated for CD64 counts at various threshold values. Results: PRU curves reduced the residual uncertainty of the presence of infection by up to 64%. Conclusions: The CD64 appears to be a useful point of care test (POCT) for further defining the likelihood of infection and performs better than CRP or PCT at helping to rule in infection.